O ensino da escrita em inglês : uma perspectiva discursiva - Barbosa, Neuzamar Marques (2015)
This study investigates the teaching of writing in English, in the context of public school and it aims to substantiate the teaching of writing in the discursive perspective, based on the Analysis of the French Discourse, and submit proposals for this teaching, given the direct effects of the writing in the improvement of orality in English language. The purpose is to promote a discussion about the need of impressing a change in the traditionally way that has been worked the teaching of English writing in public school. The present work resorts to a qualitative research methodology and was developed from one discursive perspective. The corpus was constituted by the answers of English teachers to the questionnaire and a reading activity of the didatic book. The analysis shows that there is a consolidation of the writing in the traditional perspective, which sees it as a communication tool; the writing activities in English classes are also traditional and privileges the linguistic aspects in teaching and the reinforcement of structures and vocabularies and reading is understood as a decoding process, where text is the only source of meaning, that it will be responsibility of the reader to extract it through the linguistic decoding. The results of this study suggest a change in the way of how the writing is worked, emphasizing the discursive side of the working with language. This research contributes to the teaching / learning process and the initial and continuing education of English teachers.